ANALISIS YURIDIS PELAKSANAAN PEMBEBANAN HAK TANGGUNGAN DALAM PERJANJIAN KREDIT BANK DI KOTA PONTIANAK - NIM. A1011191248, MUHAMMAD NABIL KAUTSAR PRIYANTANA (Jurnal Fatwa Hukum, 2023)
AbstractCredit has a very significant role today, because the business world is growing. Whether the trade, industry, agriculture, housing, services and others sectors, credit is a driving factor in that regard. With the credit provided by the bank, it must cause risk. Because not all debtors are good in practice. Therefore, that is what causes the need for guarantees in every provision of credit. Land rights are one type of guarantee. In Law Number 4 of 1996 concerning Dependent Rights along with objects related to land, it is determined that Property Rights, Building Use Rights, Business Use Rights can be used as debt security by being burdened with Dependent Rights. The purpose of this study is to discuss the implementation of credit agreements with guaranteed Rights of Dependents and the imposition of Rights of Dependents in credit agreements. The method used in this thesis research is a normative problem approach and is supported by field studies. The data source used is a secondary data source (legislation). Data collection method with literature study and interview. The implementation of the credit agreement is preceded by a credit application by the prospective debtor to the financial institution or bank. Then the financial institution analyzes the credit application file and the results are given to a notary. If there is a certificate that has not returned the name, it will not be accepted by the notary, and it is necessary to use a power of attorney. The legal consequences that will occur if the certificate has not been rebranded are bad debts, defaults and other legal consequences. The effort in that case is before applying for a dependent right, the new owner or debtor should consult with the competent authorities and also with the bank that will provide credit and the financial institution or bank needs to be more careful in analyzing the file. The imposition of dependent rights is preceded by the granting of dependent rights by making a Deed of Granting Dependent Rights (APHT) in PPAT. Then registration of dependent rights is carried out at the Land Office by making a land book of Dependent Rights. Proof of Right of Dependency the Land Office issues a certificate of right of dependents containing irah-irah with the words "FOR THE SAKE OF JUSTICE BASED ON THE ONE AND ONLY GOD". Thus, the certificate of liability has executory power that has legal force. Keywords: Rights of Dependents, Power of Attorney, Land Rights Guarantees, Credit Guarantees. AbstrakKredit memiliki peranan yang sangat signifikan saat ini, karena dunia usaha yang semakin berkembang. Baik sektor perdagangan, industry, pertanian, perumahan, jasa dan lain-lain, kredit menjadi faktor pendorong dalam hal itu. Dengan adanya kredit yang diberikan bank, pasti menimbulkan resiko. Karena tidak semua debitur baik dalam prakteknya. Oleh karena itulah yang menyebabkan perlunya jaminan dalam setiap pemberian kredit. Hak atas tanah menjadi salah satu jenis jaminan. Dalam Undang-Undang Nomor 4 Tahun 1996 tentang Hak Tanggungan beserta benda-benda yang berkaitan dengan tanah menentukan bahwa Hak Milik, Hak Guna Bangunan, Hak Guna Usaha dapat dijadikan jaminan hutang dengan dibebani Hak Tanggungan. Tujuan penelitian ini ialah membahas pelaksanaan perjanjian kredit dengan jaminan Hak Tanggungan dan pembebanan Hak Tanggungan dalam perjanjian kredit.Metode yang digunakan dalam penelitian skripsi ini ialah pendekatan masalah secara normatif dan didukung dengan studi lapangan. Sumber data yang digunakan adalah sumber data sekunder (perundang undangan). Metode pengumpulan data dengan studi kepustakaan dan wawancara.Pelaksanaan perjanjian kredit didahului dengan permohonan kredit oleh calon debitur ke pihak lembaga keuangan atau bank. Kemudian pihak lembaga keuangan menganalisis berkas permohonan kredit dan hasilnya diberikan ke notaris. Jika terjadinya sertifikat yang belum balik nama maka tidak akan diterima oleh notaris, dan perlu menggunakan surat kuasa. Akibat hukum yang akan terjadi jika sertifikat belum balik nama ialah kredit macet, wanprestasi dan akibat hukum lainnya. Upaya dalam hal itu adalah sebelum mengajukan hak tanggungan, pemilik baru atau debitur sebaiknya melakukan konsultasi dengan pihak yang berwenang dan juga dengan bank yang akan memberikan kredit dan pihak lembaga keuangan atau bank perlu lebih teliti dalam menganalisa berkas. Pembebanan hak tanggungan didahului pemberian hak tanggungan dengan pembuatan Akta Pemberian Hak Tanggungan (APHT) di PPAT. Kemudian dilakukan pendaftaran hak tanggungan di Kantor Pertanahan dengan dibuatkan buku tanah Hak Tanggungan. Bukti adanya Hak Tanggungan Kantor Pertanahan menerbitkan sertifikat hak tanggungan yang memuat irah-irah dengan kata-kata “DEMI KEADILAN BERDASARKAN KETUHANAN YANG MAHA ESA”. Dengan demikian, sertifikat hak tanggungan memiliki kekuatan eksekutorial yang memiliki kekuatan hukum. Kata Kunci: Hak Tanggungan, Surat Kuasa, Jaminan Hak Atas Tanah, Jaminan Kredit.